Halal Supply Chain: Assessing the Islamic Values of the Poultry Industry - Omar, Emi Normalina; Jaafar, Harlina Suzana; Osman, Muhamad Rahimi (ExcelingTech, 2019)
Values are important in influencing our principles’ and behaviors and help to create positive values in our daily life. Thus, values in Islam are vital as a guide for Muslims to be good Muslims and form better societies. These values are based on the Syariah principles which can be found in the Holy Quran which is the main reference acts as a foundation for Muslims hereafter. Occasionally, Muslims do not realize that the good things that they do in their daily activities are considered as good values from the Islamic perspective i.e. Islamic values. Thus, the current business environment of the food supply chain focusing on the poultry industry has been chosen due to the highest food consumption in Malaysia. This study found that research assessing the Islamic values and halal supply chain has received relatively little attention in the literature. Therefore, this study attempts to fill the gap by assessing the Islamic values in the halal supply chain of the poultry industry. This study focuses on the existing poultry supply chain and underlying Islamic values that exist which may assist the implementation of the halal supply chain to be resilience and sustainable in the future. The study used a qualitative approach in which deployed an in-depth interview from a case study. The case study focused on the final stage of the supply chain which is retailers’ premises.